Effect of the Nearpod-Assisted Read, Observe, Auditory, Review (ROAR) Learning Model on Mathematical Literacy Skills - Inka Mayelda Putri; Siska Andriani; Ana Risqa JL (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Mathematical literacy is a crucial competency that students must possess to meet the demands of increasingly complex mathematics learning. However, based on preliminary study results, students’ mathematical literacy skills have not yet reached optimal levels. This situation prompted the researchers to conduct a study by implementing the Read, Observe, Auditory, Review (ROAR) learning model supported by the Nearpod interactive platform. This study aims to determine the effect of implementing the Nearpod-assisted ROAR learning model on students’ mathematical literacy skills. The research method used was an experimental method of the quasi-experimental type. The study population comprised all ninth-grade students at SMP Islam Tias Bangun, consisting of three classes. Sampling was conducted using cluster random sampling, resulting in two classes selected as the study sample: an experimental class with 23 students and a control class with 25 students. The experimental class received instruction using the Nearpod-assisted ROAR learning model, while the control class used the Direct Instruction model. The research instrument consisted of a mathematical literacy test in the form of essay questions that had been tested for validity, reliability, difficulty level, and discriminative power. Data analysis was conducted through prerequisite tests, namely normality and homogeneity tests, as well as hypothesis testing using the Independent Sample T-Test with a significance level of 5%. The results of the data analysis indicate that the use of the NearPod-assisted ROAR learning model has a significant effect on students’ mathematical literacy skills. The novelty of this study lies in the integration of the ROAR learning model with the Nearpod interactive medium to encourage active student engagement and develop students’ mathematical literacy skills